1999
DOI: 10.1007/s000490050039
|View full text |Cite
|
Sign up to set email alerts
|

Fungal pathogenesis of the sea fan Gorgonia ventalina: direct and indirect consequences

Abstract: Fungal pathogenesis of the sea fan Gorgonia 6entalina has developed on the Belize barrier reef during 1997 and 1998. The disease incidence (= percent of infected sea fans) remained unchanged at two sites along the barrier reef crest between years. However, the incidence increased significantly at an offshore atoll during that time, as did the virulence ( = percent tissue loss). Grazing by the gorgonian specialist mollusc Cyphoma gibbosum increased on infected sea fans. Sea fan responses to fungal infection inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
29
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 32 publications
3
29
0
Order By: Relevance
“…34 " 35 In Gorgonia ventalina, the crude extracts are reported to be uniform throughout the colony. 261 ' 266 However, as previously discussed, crude extracts from the tips of healthy Gorgonia spp. colonies exhibited more antifungal activity against Aspergillus sydowii than extracts from other parts of the colony.…”
mentioning
confidence: 92%
“…34 " 35 In Gorgonia ventalina, the crude extracts are reported to be uniform throughout the colony. 261 ' 266 However, as previously discussed, crude extracts from the tips of healthy Gorgonia spp. colonies exhibited more antifungal activity against Aspergillus sydowii than extracts from other parts of the colony.…”
mentioning
confidence: 92%
“…Kim 1994, Slattery et al 1995, Jensen et al 1996, anti-fouling (Targett et al 1983, Standing et al 1984, Wilsanand et al 1999 anti-fungal (Kim et al 2000a,b), and/or predator (e.g. Pawlik et al 1987, Sammarco et al 1987, Harvell et al 1988, Harvell & Fenical 1989, Pawlik & Fenical 1989, Fenical & Pawlik 1991, Van Alstyne & Paul 1992, Cronin et al 1995, Slattery 1999) -and competitor (e.g. Sammarco et al 1983, Rittschoff et al 1985, La Barre et al 1986) -deterrent secondary compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Hay & Fenical 1988, Hay 1998, Van Alstyne & Paul 1989, Cronin & Hay 1996, gorgonians (e.g. Harvell & Fenical 1989, Van Alstyne & Paul 1992, Harvell et al 1993, Cronin et al 1995, Slattery 1999, Kim et al 2000a, and sponges (e.g. Paul 1992 [review], Pawlik et al 1995, Becerro et al 1998, Swearingen & Pawlik 1998) have documented significant within-species variation in secondary metabolite production.…”
Section: Introductionmentioning
confidence: 99%
“…colonies are more resistant to the fungal pathogen A. sydowii than extracts from other parts of the colony and that crude extracts inhibit spore formation at natural concentrations. Slattery 266 found that fungal infection increased the susceptibility of Gorgonia ventalina to grazing by Cyphoma gibbosum.. The furano-germacrene julieannafuran 86 263 decreased in concentration in infected colonies.…”
mentioning
confidence: 99%
“…The compound was deterrent to fish but only at levels found in pre-infected colonies. 266 In a more recent survey, crude extracts from Echinogorgia sp. C, C. cf umbraculum and S. suberosa were active against potentially invasive fungi at or near natural concentrations.…”
mentioning
confidence: 99%